Gold Talent Identifier (GTI) / Idris Osman … [et al.] - Osman, Idris; Wei Loon, Koe; Sa'ari, Juan Rizal; Md.Taib, Norraeffa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Talents are important for growth and sustainability of companies. It is undoubtedly that talent management is a complex process. The initial stage in it is, of course, identifying talents. To date, organizations are being subjective in talents identification. This has brought to various problems in human resource management, such as acquiring and retaining the "right" talents. As such, Gold Talents Identifier (GTI) is developed to serve as a tool for quick and easy talents identification. Based on the seven criteria of soft skills (Kemahiran Insaniah) initiated by Ministry of Higher Education, GTI allows the managers to conduct evaluation on existing and potential employees' soft skills. Then, individuals are categorized into "Gold", "Silver" or "Bronze" categories. From there, the “right" talents can be easily identified, acquired and retained. Main advantages of using GTI are such as cost saving, easy to use and non-subjective. Although GTI is not a comprehensive and exhaustive tool for talent identification, it does help to assess individuals' soft skills. For future development, GTI can be developed into electronic version.